A functional network of gastric-cancer-associated splicing events controlled by dysregulated splicing factors. Issue 2 (28th February 2020) - Cheng, Shanshan; Ray, Debleena; Lee, Raymond Teck Ho; Naripogu, Kishore Babu; Yusoff, Permeen Akhtar Bt Mohamed; Goh, Pamela Bee Leng; Liu, Yujing; Suzuki, Yuka; Das, Kakoli; Chan, Hsiang Sui; Wong, Wai Keong; Chan, Weng Hoong; et al.
Abstract: Comprehensive understanding of aberrant splicing in gastric cancer is lacking. We RNA-sequenced 19 gastric tumor–normal pairs and identified 118 high-confidence tumor-associated (TA) alternative splicing events (ASEs) based on high-coverage sequencing and stringent filtering, and also identified 8 differentially expressed splicing factors (SFs). The TA ASEs occurred in genes primarily involved in cytoskeletal organization. We constructed a correlative network between TA ASE splicing ratios and SF expression, replicated it in independent gastric cancer data from The Cancer Genome Atlas and experimentally validated it by knockdown of the nodal SFs ( PTBP1, ESRP2 and MBNL1 ). Each SF knockdown drove splicing alterations in several corresponding TA ASEs and led to alterations in cellular migration consistent with the role of TA ASEs in cytoskeletal organization. We have therefore established a robust network of dysregulated splicing associated with tumor invasion in gastric cancer. Our work is a resource for identifying oncogenic splice forms, SFs and splicing-generated tumor antigens as biomarkers and therapeutic targets.